Plenty of (Similar) fish in the sea: The role of social identity and self-categorization in niche online dating. (September 2020) - Hernandez, Terri; Sarge, Melanie A.
Abstract: Political partisanship fosters in-party dating behaviors. However, little research has explored why individuals employ homogenous approaches (e.g., political homophily) to partner selection and their role in initiating, developing, and sustaining romantic relationships. The present study posits that social identity theory (SIT) and self-categorization theory (SCT) provide explanations for this phenomenon in an online dating context. Specifically, niche online dating websites (e.g., Liberal Hearts, Farmers Only, Active Singles) provide an environment ripe with group dynamics. These websites emphasize a characteristic that a group of individuals share and associate with their self-concept. Theoretically, the social identity formed around this characteristic becomes situationally accessible and serves as the dominant factor by which individuals evaluate and categorize others (i.e., potential online partners in the present context). In an online survey experiment, participants viewed a dating website tailored to a political affiliation (congruent or incongruent to their own affiliation), selected a user's profile to browse and evaluated them as a potential romantic partner. Results revealed expectations of relationship satisfaction and willingness to date were influenced by group membership directly and indirectly through perceptions of trustworthiness. The extent to which the partner's values aligned with the group moderated this indirect effect. Highlights: Niche online dating websites provide an environment ripe with group dynamics. Realistic political niche online dating stimuli modeled after existing websites. Ingroup membership can increase favorable relationship expectations and intentions. Novel examination of intragroup processes in an online dating context. Greater trust of and preference for ideal representations of ingroup members.